Impact of climate change on agriculture in Kazakhstan - Islyami, Aidan; Aldashev, Alisher; Thomas, Timothy S.; Dunston, Shahnila (University of Westminster Press, 2020)
Using the Global IMPACT model, we investigate the probable effect of climate change on the performance of agriculture and socio-economic conditions in Kazakhstan under five climate-change scenarios. These include a baseline and four climate-change scenarios (MIROC, Hadgem, GFDL, and IPSL) from the Intergovernmental Panel on Climate Change (IPCC). More specifically, we focus on climate-change impact on the production of wheat, potatoes, cotton, maize, rice, and barley. The results suggest that increased temperatures and precipitation will hurt spring crop yields such as wheat and barley. Climate change will probably positively impact the yields of winter varieties of wheat and barley and enable farmers to practise multiple cropping during a farming season. Rice yield is also expected to increase due to climate change, but the yield of potatoes is projected to be adversely affected. Therefore, climate change will be one of the critical challenges for improving agricultural productivity, household welfare, and ensuring food and nutrition security in Kazakhstan.